Computing Self-Supporting Surfaces by Regular Triangulation - Liu, Yang; Pan, Hao; Snyder, John; Wang, Wenping; Guo, Baining (ACM Transactions on Graphics (TOG) - SIGGRAPH 2013 Conference Proceedings, 2013)
Masonry structures must be compressively self-supporting; designing such surfaces forms an important topic in architecture as well as a challenging problem in geometric modeling. Under certain conditions, a surjective mapping exists between a power diagram, defined by a set of 2D vertices and associated weights, and the reciprocal diagram that characterizes the force diagram of a discrete self-supporting network. This observation lets us define a new and convenient parameterization for the space of self-supporting networks. Based on it and the discrete geometry of this design space, we present novel geometry processing methods including surface smoothing and remeshing which significantly reduce the magnitude of force densities and homogenize their distribution.